DEVELOPMENT OF TECHNOLOGY FOR EXTRACTION OF NON-FERROUS METALS FROM CONVERTER DUST - Shodiev A. N,; Ravshanov A. A. (Scholars Digest Publishing, 2023)
This article considers the relevance of processing fine dusts containing valuable components such as copper, zinc and lead. The existing methods are analyzed, and the parameters of technology for obtaining lead as a result of studying and researching the dust generated during the purification of waste gases of the process of smelting flotation concentrates and converting copper matte of the smelting plant of Joint Stock Company "Almalyk mining and smelting plant". Having studied the chemical composition of converter dust and based on its chemical and physical properties the rational technological scheme for its processing has been developed. According to the suggested technological scheme at the first stage zinc and copper are transferred into solution by sulfuric acid leaching. From the remaining cake lead is first transferred into a salt solution and then precipitated by carbonization in the form of lead carbonate, which is first filtered and washed, then calcined and melted in a reducing medium to obtain metallic lead.
Keywords: man-made waste, dust, leaching, pyrometallurgy, hydrometallurgy, sulfuric acid, salt, carbonization, separation, solution, sludge, technological scheme.